Prevalence of mental health problems and their potential association with sleep disturbance, coping skills and social support in professional ballet dancers - Junge, A.; Hauschild, A. (Journal of Dance Medicine & Science, 2024)
Introduction: While several studies have analyzed the characteristics and burden of injuries and physical complaints in (pre-)professional dancers, mental health problems, other than eating disorders, have rarely been studied in professional ballet dancers. The aims were to (a) investigate the prevalence of self-reported mental health problems, and (b) analyze their potential associations with sleep disturbance, coping skills and social support in professional ballet dancers.